Efektivitas Edukasi Online dalam Meningkatkan Pengetahuan Kesehatan pada Wanita - Handayani, Lina; Vergawita, Tania; Nisa Novianti, Tria; Sutikno, Tole (Apik Cahaya Ilmu, 2025)
Health knowledge is a fundamental factor in maintaining the well-being of individuals and communities. Women play a central role as agents of change in promoting healthy lifestyle behaviors. This activity aims to conduct online health education to improve women's health knowledge. The educational intervention was conducted online, covering topics such as healthy lifestyles, women's roles, and the creation of a healthy generation, accompanied by pretests and posttests to assess changes in knowledge. The results showed a significant increase in knowledge scores, from an average of 3.94 to 4.76 after the intervention (p < 0.05). Online education offers advantages such as ease of access, time flexibility, and empowerment potential for women who often carry dual roles in both family and community settings. However, challenges remain, including internet access limitations and the lack of face-to-face interaction. Online health education has proven effective in enhancing women's health knowledge and should be further developed through improved technical infrastructure and diverse educational content to ensure sustainable long-term impact.